2014
DOI: 10.5812/numonthly.19976
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Microvascular Complications in Patients With Type 2 Diabetes Mellitus

Abstract: Background:Although chronic kidney disease-induced anemia is more prevalent in patients with diabetes mellitus (DM), anemia is a common finding prior to manifestation of kidney disease. In presence of some risk factors at the time of diagnosing DM, microvascular complications must be considered. The effect of anemia as a risk factor on progression of DM complications is still unclear.Objectives:The aim of the study was to determine the prevalence of anemia and its association with microvascular complications i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
45
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 29 publications
18
45
4
3
Order By: Relevance
“…In the Predialysis Survey on Anemia Management (PRESAM) involving patients with advanced nephropathy, 2 diabetes did not increase the risk of anemia, but other studies from a variety of countries have shown that between 14% and 45% of patients with diabetes are anemic. [3][4][5][6][7][8] Notwithstanding the PRESAM data, this discrepancy may reflect differences in the proportions with renal impairment since the prevalence in outpatients with normal renal function (estimated glomerular filtration rate (eGFR) N 60 mL/min/ 1.73 m 2 ) has been estimated at only 10%. 9 An apparent diabetes-specific risk of anemia has been attributed to reduced responsiveness to erythropoietin (EPO).…”
Section: Introductionmentioning
confidence: 99%
“…In the Predialysis Survey on Anemia Management (PRESAM) involving patients with advanced nephropathy, 2 diabetes did not increase the risk of anemia, but other studies from a variety of countries have shown that between 14% and 45% of patients with diabetes are anemic. [3][4][5][6][7][8] Notwithstanding the PRESAM data, this discrepancy may reflect differences in the proportions with renal impairment since the prevalence in outpatients with normal renal function (estimated glomerular filtration rate (eGFR) N 60 mL/min/ 1.73 m 2 ) has been estimated at only 10%. 9 An apparent diabetes-specific risk of anemia has been attributed to reduced responsiveness to erythropoietin (EPO).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, falsely decreased results are obtained from patients treated with iron preparations, vitamin B 12 , folic acid, erythropoietin, vitamins C and E. Similar effects are reported in conditions with shortened erythrocyte lifespan -i.a massive blood loss, hemolytic anemias -and hemoglobinopathies, splenomegaly, chronic liver diseases, in chronic alcohol drinkers, patients with hypertriglyceridemia, rheumatoid arthritis and retroviral therapy subjects [11][12][13][14][15][16].…”
Section: Glycated Hemoglobin (Hba 1c )mentioning
confidence: 54%
“…Falsely elevated HbA 1c values are also observed in patients with vitamin B 12 , folic acid and iron deficiency anemiae, in chronic kidney disease, hyperbilirubinemia, in patients using acetylsalicylic acid in large doses, opiate users, post splenectomy patients and those with abnormal erythrocyte structure (lower than usual erythrocyte pH, longer erythrocyte lifespan) [11][12][13][14][15][16]. Conversely, falsely decreased results are obtained from patients treated with iron preparations, vitamin B 12 , folic acid, erythropoietin, vitamins C and E. Similar effects are reported in conditions with shortened erythrocyte lifespan -i.a massive blood loss, hemolytic anemias -and hemoglobinopathies, splenomegaly, chronic liver diseases, in chronic alcohol drinkers, patients with hypertriglyceridemia, rheumatoid arthritis and retroviral therapy subjects [11][12][13][14][15][16].…”
Section: Glycated Hemoglobin (Hba 1c )mentioning
confidence: 99%
“…[10][11][12] Prevalence of anemia is estimated about 10-30% in patients with diabetes. [13] The etiology of anemia in diabetics is multi-factorial and includes inflammation, nutritional deficiency, concomitant autoimmune diseases, drugs, hormonal changes in addition to kidney disease. Approximately one-third of patients with anemia exhibit iron deficiency.…”
Section: Discussionmentioning
confidence: 99%